The Development of Student’s Worksheet Integrated with Estacol and Picture-and-Picture Method as the Altenative Teaching Material of Writing Short Story During Pandemic Covid-19 - Durratul Baidha; Cut Siti Raihan; Nurul Hasanah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
This study aims to produce a Student’s Worksheet which is integrated withwriting short story and it is integrated in relay collaborative writing (estacol) and picture-and-picture method in the Fiction Prose Course. The method of this research used the research and development ADDIE model. The subjects involved in this study were 27 FKIP students of the Department of Indonesian Language Education. The expert validators in this study were two literature lecturers. The data of this research were obtained from experts’ validation toward questionnaires and students questionnaire responses. The result of this study indicated that the eligibility validated by experts was in a very good range with 98,9% of percentage. The students’ response toward questionnaire also received an overall value of the results that were very suitable to be used with an 85% average as the feasibility without revision. As such, the Student’s Worksheet developed was suitable to be used as learning material for short story writing during pandemic Covid-19.